The library is open: a scoping review on queer representation in psychedelic research - Bartlett, Amy; Christ, Challian; Martins, Bradford; Saxberg, Kellen; Ching, Terence H. W. (Frontiers in Public Health, 2024)
The intersection of queer identity and psychedelics has not been thoroughly explored by the research community, historically or in the present day. With growing access to legal psychedelic therapies, it is essential that queer psychedelic experiences are understood sufficiently by clinicians in order to provide the most safe and effective care possible. Psychedelics and queerness are intricately related, and there is strong interest in the use of psychedelics for healing and identity development among queer populations. However, the vast majority of the literature stigmatizes and problematizes queer psychedelic use. Therefore this scoping review seeks to explore the current and historical overlap between psychedelics and queerness in the academic literature. Specifically, this scoping review aims to understand the available academic literatures’ treatment of the meaningful, non-pathologizing use of psychedelics within the queer community, and seeks to highlight the unique potential a queer lens and the queer experience can bring to the study of psychedelics. To do so, we asked what queer psychedelic experiences are reflected in the literature, who is being studied, what queer individuals’ motivations are for using psychedelics, and a review of the impacts of queer psychedelic use discussed in the literature. Literature searches were performed in seven academic databases using a wide breadth of both queer-related and psychedelic-related keywords, which resulted in over thirty thousand resources being captured. After screening, a total of 18 resources were collected as representative of the meaningful overlap of psychedelics and queerness. Based on the findings and research gaps identified, this scoping review makes several recommendations regarding future directions psychedelic researchers and clinicians can pursue to better understand and benefit from the meaningful overlap of psychedelics and queerness. By reclaiming, redefining, and reimagining the meaningful relationship between psychedelics and the queer experience, this review helps move the scientific and clinical conversation into queerer spaces, centering queerness and queer experiences as an essential component of psychedelic research and practice.